2020
DOI: 10.1371/journal.pone.0242922
|View full text |Cite
|
Sign up to set email alerts
|

The risk of stroke/systemic embolism and major bleeding in Asian patients with non-valvular atrial fibrillation treated with non-vitamin K oral anticoagulants compared to warfarin: Results from a real-world data analysis

Abstract: Background Although randomized trials provide a high level of evidence regarding the efficacy of non-vitamin K oral anticoagulants (NOACs), the results of such trials may differ from those observed in day-to-day clinical practice. Aims To compare the risk of stroke/systemic embolism (S/SE) and major bleeding (MB) between NOAC and warfarin in clinical practice. Methods Patients with non-valvular atrial fibrillation (NVAF) who started warfarin/NOACs between January 2015 and November 2016 were retrospectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 36 publications
7
19
0
Order By: Relevance
“…In another study evaluating the effectiveness and safety of NOACs versus warfarin among the Korean population with AF, NOACs had an overall favorable clinical benefit compared to that of warfarin, although 50-75% of the cohort included patients on reduced-dose NOAC treatment [17]. Similar results were obtained from our previous study in which the risk of S/SE and MB were compared between NOACs (including all dosages) and warfarin in the OAC taking AF patients [35]. Considering that reduced dosing is recommended for patient groups associated with a higher risk of not only bleeding (HAS-BLED) but also for stroke (CHA 2 DS 2 -VASc), this study's results provide additional information on the benefit of NOACs over warfarin in Asian patients requiring anticoagulation for stroke prevention.…”
Section: Discussionsupporting
confidence: 69%
“…In another study evaluating the effectiveness and safety of NOACs versus warfarin among the Korean population with AF, NOACs had an overall favorable clinical benefit compared to that of warfarin, although 50-75% of the cohort included patients on reduced-dose NOAC treatment [17]. Similar results were obtained from our previous study in which the risk of S/SE and MB were compared between NOACs (including all dosages) and warfarin in the OAC taking AF patients [35]. Considering that reduced dosing is recommended for patient groups associated with a higher risk of not only bleeding (HAS-BLED) but also for stroke (CHA 2 DS 2 -VASc), this study's results provide additional information on the benefit of NOACs over warfarin in Asian patients requiring anticoagulation for stroke prevention.…”
Section: Discussionsupporting
confidence: 69%
“…Several studies and meta-analyses (14,15) have described aspects of the anticoagulation of AF with RWD data, although the results sometimes are misleading due to the lack of uniformity of the studies selected in the meta-analysis. The majority compared the performance of the NOACs with the VKA in terms of risk reduction of stroke or major bleeding events (9.11, 12, 14, 16), with or without applying propensity score matching (9). Our results emphasize the importance of anticoagulation to reduce stroke incidence, cardiovascular, and total mortality.…”
Section: Discussionmentioning
confidence: 88%
“…Although randomized trials provide evidence on the efficacy of anticoagulant treatments, the results may differ from those observed in daily clinical practice. Using real-world data (RWD), the impact of anticoagulant therapy has been analyzed using different sources (9)(10)(11)(12)(13)(14)(15). Electronic health records (EHRs) collect a large amount of information, including data about prevalence, disease control, risk factors, treatments, modifying conditions, and information for surveillance programs (16,17).…”
Section: Introductionmentioning
confidence: 99%
“… 6 Recently, a retrospective study in Asian patients showed that dabigatran was associated with a significantly lower stroke/systemic embolism risk and lower major bleeding risk than warfarin. 22 Taken together, our results suggested that an over inhibition of TG may not be necessary for the prevention of thromboembolism, but it would increase the incidence of hemorrhagic events. It is useful to understand the meaning of TG in clinical practice.…”
Section: Discussionmentioning
confidence: 56%